San Juan Islands wilderness proposal : Smith Island, Jones Island, Matia Island, and San Juan National Wildlife Refuges, Washington - United States. Bureau of Sport Fisheries and Wildlife (Portland, Or. : The Bureau, 1971)
Provenance: George Marshall. Cover title. Mode of access: Internet.